Consumption in Architecture - Ibrahim Jawad Kadhim Alyusif; Ahmed Salim Khalaf (Iraqi Journal of Architecture and Planning, 1970)
Architectural trends and their developments witnessed new ideas at many levels; one of these ideas is known as consumption, which is one of the new themes in an old concept and in its presence, which takes place effective today in the field of architecture. And plays a role in changing the architectural constants targets, and plays a role in changing the architectural constants targets, or classification of priorities. Every body tries to search for new and evolving architecture through what is available has advanced technological methods. This will be directed Search, make the process of change and evolution in architecture is not only very close and meet human needs, but to make the first need produce innovative and creative architecture. Determine the general direction of search in the consumption of meaning forms in architecture The research theoretical knowledge for consumption in architecture, as Figure concept of evolution, and the need to study technology and its relationship with both local architecture and globalization. And a global review of various studies to try to reach the first step of the research problem of (knowledge before about formats consumption in meaning and form in the context of local architecture). And thus produced the aim of the research, to clarify the concept of consumption in architecture, through, to clarify the presence of consumption in the local architecture, and the potential to achieve consumption in the local architecture. Knowledge has helped to enrich the architectural framework of research and the formation of his variable, enhanced architectural studies available to achieve a theoretical framework integrated, variable has been to, the consumption component, and intellectual attitudes towards consumption, and forms adopted, and detailed processes. To use variable, has helped in the application on projects elected, so as to achieve a comprehensive conception of the nature of the relationship between variables, when applied collectively elected on samples of the application. The research found that consumption is a copy of the forms, and unconsumption is a simulation and new styles of architecture and context beyond.